Introduction: Weaving Codes, Coding Weaves. (3rd April 2017) - McLean, Alex; Harlizius-Klück, Ellen; Jefferies, Janis
Abstract: This article introduces the TEXTILE special issue on Weaving Codes, Coding Weaves, and the project of the same name, which was funded by the Arts and Humanities Research Council for 18 months from September 2014. We introduce the collaborators of this interdisciplinary project, spanning textiles, music, arts technology, computer science, mathematics, anthropology, media theory, and philosophy. We tell the multifaceted story of how we met and began to collaborate, following prescient activities in textiles, music performance, live art, and computer programming that have met confluence in our project. This forms an introduction to the articles produced by these collaborators, either as part of the Weaving Codes project, or in parallel with it. We conclude by looking to the future, in particular the five year ERC PENELOPE project now beginning in the Deutsches Museum in Munich.